Does Credit Card Usage Enhance Defaults among Compulsive Buyers? - Alex, Joji; Raveendran, P. T. (Indian Journal of Marketing, 2011)
The Indian society is transforming, with an increasing exhibition of materialistic behaviour, and varied diversity of interests and preferences as consumers. In a rapidly emerging retail and credit card marketplace, the research question is to ascertain the impact of materialism, compulsive buying, credit card spending and financing behaviour on credit default. The respondents were those using the credit cards for a period greater than one year and structural equation modelling is used to meet the objectives. The findings reveal that credit default is a result of compulsive buying. The credit card financing behaviour is also enhancing the rate of defaults. The practical implication is that the financial retailers should increase customer suitability in the retail sale of credit cards to limit future default rate.